Implementing a land value tax: Considerations on moving from theory to practice. (May 2020) - Hughes, Cathy; Sayce, Sarah; Shepherd, Edward; Wyatt, Pete
Highlights: The theoretical case for land value taxation (LVT) is compelling yet uptake is not widespread. Political and practical considerations are important when implementing LVT. LVT needs to be linked to a robust land ownership register. LVT requires valuations which separate land value from the value of improvements. Such practical issues create uncertainty compared with existing taxes. Abstract: A land value tax is a recurrent tax on landowners based on the value of unimproved land. There is a widely held view that a land value tax is an economically efficient means of taxing wealth and of encouraging land development. The arguments presented in the policy and academic literature tend to concentrate on the compelling theoretical case, but most do not consider the detail of how such a tax might be implemented. Indeed, land value taxation is not widely implemented as a standalone real estate tax despite the strong theoretical rationale for its use. We explore why this might be by identifying key practical, political and economic factors surrounding the implementation and operation of land value taxation in six countries. We examine the various rationales for the introduction of land value tax, reasons for its continued use or abolition (where applicable) as well the particular practical and political issues which policymakers need to consider prior to introducing land value taxation. These include the need for a comprehensive up-to-date land registry and forward planning of land use at plot level; the provision of a well-resourced and informed valuation profession; resources to undertake robust valuations which separate the value of land from the value of improvements for developed plots and do so on the basis of highest and best use; and the need for widespread political support for the introduction of a new tax (which may be difficult to secure). These issues present significant uncertainty in comparison with already-existing forms of land and property taxation. We conclude that these issues may therefore provide some explanation as to the lack of widespread adoption of land value tax despite the economic theoretical arguments in its favour.